Sistem Informasi Reminder Service Kendaraan Roda Empat dengan Teknologi Whatsapp Gateway Berbasis Website - Asep Sumantri; Zahwa Oktaviani; Deni Kurniawan (Pusat Riset dan Inovasi Nasional, 2025)
This research was motivated by vehicle users who did not remember when to service their vehicle, causing damage to the vehicle. Therefore, a system is needed to provide information about vehicle service schedules using electronic media, one of which is WhatsApp messages. This research was conducted at TOMO Pondok Mahkota Motor. The research method is a quantitative method. The data collection techniques used were interviews, observation and questionnaires. In preparing this application system, the UML method was used. Application development using the PHP programming language and preparation of database structures using MySQL. The research results show that this system is useful for recording customer data, providing information on the next four-wheeled vehicle service schedule to customers, customers find out information on the next four-wheeled vehicle service schedule via WhatsApp notifications.